Hazard identification and safety goals on power electronics in hybrid vehicles - Walderyd, Fredrik (My University, 2010)
The task of this master thesis has been to implement part 3 of ISO26262 into Haldex new eTVD, electric torque vectoring drive. It is an electrical rear axis for a passenger car. This is a stage in the more environmental friendly vehicle industry. ISO26262 is a new, soon to be released standard for safety of the using of electrical equipment within the car. ISO26262 is a new safety standard for E/E-system (electronic/electrical-system) within the car, developed in collaboration with different car manufactures. Many of them will demand the suppliers to implement ISO26262. The purpose is to work for a common standard for the safety. A first release of the standard will be probably be in the start of year 2011. Today we are in the draft stage and after this the final draft will be assigned. The Swedish name for ISO26262 will probably be SS-ISO26262.
Keywords: Elkraftteknik; Electric power engineering